Introduction to criminology: why do they do it? - Schram, Pamela (SAGE, 2018)
Introduction to criminology -- Measuring crime -- Classical school of criminology thought -- Contemporary classical and deterrence research -- Early positivism -- Modern biosocial perspectives of criminal behavior -- Psychological/trait theories of crime -- Social structure theories of crime i -- Social structure theories of crime ii -- Social process and control theories of crime -- Labeling theory and conflict/marxist/radical theories of crime -- Feminist theories of crime -- Developmental/life-course perspectives criminality -- White-collar crime, organized crime, and cybercrime -- Hate crimes, terrorism, and home -- Drugs and crime -- Key terms -- Student study site -- Discussion questions -- Web resources